Button Mushroom Farming: A Critical Review - Jeyaprabha J; Mudhalvan S; Vijayakumar S (Archives of Current Research International, 2025)
Button mushroom (Agaricus bisporus) stands as the most widely cultivated edible mushroom globally, owing to its nutritional value, rapid growth cycle, and adaptability to various substrates. This review explores various aspects of button mushroom production, including cultivation methods, substrate utilization, pest and disease management, and socio-economic impacts. The cultivation process is systematically categorized into composting, spawning, casing, and crop management. Pest and disease management remains a critical component, with challenges like Verticillium dry bubble and green mould affecting yield and quality. Economically, button mushroom farming has demonstrated significant potential, especially for small-scale and marginal farmers. Studies indicate that with appropriate training and access to quality inputs, farmers can achieve substantial returns, thereby improving their socio-economic status. Nutritionally, they are low in calories and high in essential nutrients, including B-vitamins, minerals like potassium and phosphorus, and dietary fiber, contributing to heart health, immune support, and metabolic function. Medicinally, button mushrooms possess antioxidant, anti-inflammatory, and anticancer properties, with bioactive compounds like ergothioneine and polysaccharides showing potential in disease prevention and treatment. Economically, button mushroom farming offers profitability, especially for small-scale farmers, by providing a sustainable source of income and contributing to rural development. This review underscores the multifaceted value of button mushrooms and highlights the need for continued research to optimize cultivation practices, enhance medicinal applications, and improve postharvest handling to meet global demand.